Drug-related problems among breastfeeding patients treated for depressive spectrum disorders - Morze, Karolina; Szałek, Edyta; Waszyk-Nowaczyk, Magdalena (Frontiers in Pharmacology, 2024)
mothers (25.5%) reported adverse events in their infants, but after causality evaluation, only four (8.5%) might have been linked to maternal medication. None required medical intervention beyond one hospitalization for a serious adverse event possibly connected to maternal medication.The study identified high rates of medication-related problems among breastfeeding mothers with depression, primarily due to non-adherence. Pharmacist interventions significantly improved DRP outcomes. Adverse events were reported, but most were mild and did not require intervention. Our findings suggest that lactating mothers with depression may benefit from pharmacist-led support to optimize treatment adherence and address medication safety concern.